How management consultants influence processes of stratetic change within organisations : An enactment perspective - Pellegrinelli, Sergio (Cranfield University, 2000)
The view that individuals and organisations create or enact their social worlds through shared frames of reference, on-going interlocking routines and patterns of action is increasingly underpinning academic research and offering practitioners new insights. At the same time, now commonplace strategy consultancy services are rooted in the rhetoric, if not the practice, of rational, technical analysis. This research explores the influence of management consultants in helping managers to create as well as discover the environment they experience and to develop and realise a strategic direction for their organisations. Grounded in four diverse case studies, the research offers a richer, inextricably contextual and essentially social conception of consultants’ strategy interventions. Consultants’ work is conceived as simultaneously embedded or set within, yet seeking to achieve a separation from, existing organisational frames of reference, commitments and routines. By creating and maintaining some degree of separation, consultants facilitate a distinct enactment or experience of the world, and so influence the strategic thinking and subsequent actions of managers. Efforts to achieve separation are met by pressures to conform, and the ideas generated merge into the wider organisational enactment. The research points to complex processes of reciprocal influence, positioning and resistance between consultants and members of the organisation which shape the nature and course of an intervention. It also sheds light on the ripple effect interventions have through an organisation, on how new strategies are diffused and fused within existing patterns of thought and action, and the process of strategic change and transformation. The theoretical framework developed, comprising the concept of embedded enactment and two overarching dimensions of separation and absorption, provides a new way of understanding and explaining consultants’ strategy interventions. The case studies themselves describe some subtleties and nuances of interventions and offer opportunities for consultants and managers to reflect on personal experiences.